Accommodative and binocular characteristics in myopes with age-related accommodation deficiency - Ruiyu Zhang; Yifei Yuan; Yu Zhang; Yueguo Chen (BMC Ophthalmology)
Abstract Background To investigate accommodative and binocular characteristics in myopic patients with age-related accommodation deficiency, and to investigate the relationship of accommodation amplitude (AA) with other accommodative and binocular parameters. Methods Myopic patients between 40 and 50 years old to undergo refractive surgery were enrolled. Accommodative function, including AA, positive and negative relative accommodation (PRA and NRA), accommodative response (binocular cross cylinder, BCC), and binocular accommodative facility (BAF) were examined. Binocular vision measurements including simultaneous perception, fusional vergence, and stereovision assessed with a synoptophore. Near point of convergence (NPC) and the gradient accommodative convergence/accommodation (AC/A) ratio were also measured. A questionnaire was used to assess subjective visual discomfort experienced after prolonged near work. Results A total of 145 subjects were evaluated, with a mean age of 42.59 ± 2.89 (SD) years. In the full data set, 96(66.21%) of patients had PRA (>-1.50 D), 21(14.48%) of patients had NRA (< 1.50 D), and 113(77.93%) of patients had BCC (< 0.25 D). Out of 97 patients, 17(17.53%) had AC/A (< 2), 54(55.67%) had NPC (> 7.5 cm), 51(52.58%) had BAF (< 5 cpm). As for the simultaneous perception, 59(60.82%) had values greater than 0 prism dioptres. Adjusting for associated factors, participants with lower AA were more likely to be older (odds ratio [OR], 2.080; 95% confidence interval [CI], 1.523–2.841) and with milder myopia (OR, 1.280; 95% CI, 1.029–1.594). Lower BAF (OR, 4.990; 95% CI, 1.731–14.386) was more likely to be found in individuals with lower AA. The three most commonly reported visual discomforts were eye strain or soreness, ocular pain or headache, and blurred text. Conclusion For myopes at the early stage of presbyopia, the continuous tension in the vergence system was also worthy of our attention, in addition to the well-known AA insufficiency. Comprehensive assessment of the binocular status and appropriate management is recommended before and after corneal refractive surgery.